A COST - COMPARISON OF THE USE OF INFLUENZA VACCINE IN OLD AGE HOME RESIDENTS IN JOHANNESBURG - Cobb, Hugh (My University, 2006)
Residents of old age homes are at increased risk for the complications of influenza. Studies in developed countries have consistently shown that influenza vaccination of old age home residents and staff can significantly decrease morbidity and mortality rates and that influenza vaccination is one of the most cost effective interventions possible in this population. No studies have been done on the cost benefit of using influenza vaccine in old age home residents in South Africa. The aim of this study was to evaluate the costs of treating influenza and influenza-like illnesses in old age home residents, and to compare the costs in people who had received the influenza vaccine to those who had not. The study population comprised 151 people residing in two old age homes in Johannesburg, namely Sandringham Gardens and Nazareth House. The study population was divided into two groups- those who received influenza vaccine and those who had not been vaccinated. The residents of Nazareth House who gave consent had all been vaccinated. The subjects at Sandringham Gardens were sub- divided into two groups, namely: “Residents” and “Frail care / wards” section. The general health of the “Frail care” people was poorer than that of the “residents”. Medical records were reviewed, and details of the number of doctor consultations, medication and physiotherapy prescribed, special investigations performed and hospital referrals related to influenza and influenza-like infections were recorded. The costs were then calculated using “medical aid rates”. There were no significant differences in the treatment costs, comparing those who had been vaccinated to those who had not been vaccinated. There are a number of possible explanations for this. These include, most importantly, a low to moderate epidemic activity of influenza in the season that the study was conducted. Other explanations are low patient numbers, the use of symptoms for diagnosis and the use of over the counter therapy. Despite the findings in the present study, the international literature supports the view that influenza vaccination is a cost-effective intervention in the older adult population, particularly those at higher risk. These findings have been implemented in the official guidelines of many countries, including the South African Adult Influenza Vaccination Guideline.
M Family Medicine research report - Faculty of Health Sciences
Keywords: old age home residents; influenza; influenza vaccination; South Africa; costs of treating influenza; influenza-like illnesses; compare; costs